Highly Bright and Compact Alloyed Quantum Rods with Near Infrared Emitting: a Potential Multifunctional Nanoplatform for Multimodal Imaging In Vivo. (1st April 2014) - Gao, Duyang; Zhang, Pengfei; Sheng, Zonghai; Hu, Dehong; Gong, Ping; Chen, Chi; Wan, Qian; Gao, Guanhui; Cai, Lintao
<x xml:space="preserve">Abstract</x> Controlling synthesis of near‐infrared emitting quantum rods (QRs) for in vivo imaging is a major challenge in the fabrication of multifunctional nanoprobes. Here, a reliable synthetic approach for CdTexSe1–x/ZnS alloy nanocrystals to achieve highly bright (quantum yields up to 80%) with controllable rod‐shape and near‐infrared (650–870 nm) emission is developed. Aspect ratio and emission of QRs are correlated with composition, which can be easily tuned by changing Te and Se mole ratio. It illustrates that the content of Se plays an important role in maintaining the rod‐shape, while Te has a significant impact on emitting of the nanorods. Besides exhibiting great stability over a broad range of pH (4–10) and ion strength (up to 2 mol L‐1 NaCl solution), these hydrophilic QRs display good photo stability and storage stability. In particular, the specially absorbing of paramagnetic gadolinium ions on the QRs lead to a versatile method to engineer multimodal imaging nanoprobes, which are applied for in vivo lymph node dual‐modal imaging (fluorescence and magnetic resonance imaging). These results suggest a promising strategy for engineering multifunctional imaging nanoprobes with the stable near‐infrared QRs.